Modeling the Effects of School Resources and School Climate on Students’ Cognitive Achievement in Chemistry - Sudarto M Abukasim; Faujia Umasugi; Jadaf Dahlan (Universitas Negeri Makassar, 2026)
This study examined the relationships among school resources, school climate, and students’ cognitive achievement in chemistry using a Structural Equation Modeling (SEM) approach. The study employed a quantitative survey design involving senior high school students from several districts/cities in North Maluku Province, Indonesia. Data were collected through questionnaires measuring school resources and school climate, as well as a chemistry cognitive achievement test. Instrument validity and reliability were evaluated using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Composite Reliability (CR), Average Variance Extracted (AVE), and Cronbach’s Alpha.The findings revealed that school climate had a positive and significant effect on students’ cognitive achievement in chemistry, whereas school resources did not demonstrate a significant direct effect on cognitive achievement. In addition, school resources were positively correlated with school climate. The SEM model demonstrated acceptable goodness-of-fit, indicating that the proposed structural model adequately represented the relationships among the variables. These findings suggest that supportive academic and physical school environments play a more important role in improving students’ chemistry achievement than the mere availability of institutional resources. The study highlights the importance of strengthening school climate to support students’ cognitive development and academic performance in chemistry education.